MENGANGKAT POTENSI LOKAL MELALUI HYPERLOCAL COMMUNICATION - Itsna Hidayatul Khusna; Edi Santoso; Sri Pangestuti; Mite Setiansah; Wiwik Novianti; Tri Nugroho Adi (Jurnal Pustaka Komunikasi, 2022)
Banyumas Regency is an area that has begun to develop village potency with its attention in village tourism. The problem is in the lack of community's role on promoting tourism potential. Hyperlocal communication is a technology that can help communities to introduce their potency. Hyperlocal communication can be found on social media, social networks us such as whatsapp, search engines, or websites. This study tries to explore the use of hyperlocal communication for the promotion of Taman Lazuardi, and to see community participation in developing the potential of their village. The purpose of this research is to find out what hyperlocal communication media is used by the manager of Taman Desa Lazuardi and how the role of the community on promoting the potential of their village. This study uses qualitative methods and descriptive data analysis. From the data obtained through interviews and focus group discussions (FGD), the researchers found: (1) the media used for promotion of the Taman Desa Lazuardi is Instagram, (2) the manager's strategy in utilizing Instagram is to create interesting content, and collaborate with content creators to promote Taman Desa Lazuardi, and (3) community role enhancement in promoting village potential.